Envolvimento do sistema renina angiotensina aldosterona e de vias gabaérgicas e glutaminérgicas no aumento da retenção gástrica induzida por exercício físico agudo em ratos - Cavalcante, Ana Karolina Martins (2021)
We have previously shown that acute physical exercise (EFA) delays gastric emptying (EG) of liquid in rats, a phenomenon that was abolished by pretreatment with sodium bicarbonate and related to vipergic and nitregic pathways. The present study aimed to investigate the involvement of the Renin Angiotensin Aldosterone System (RAAS) and of gabaergic and glutaminergic pathways in the increase of gastric retention induced by acute exercise in rats. Wistar rats, weighing between 200 and 280g, were used. The EFA protocol consisted of a period for adaptation to a water tank for 5 days (10- 40min), with the animals undergoing fasting on the sixth day, followed by a single swimming session with an overload of 5% of body weight. or not. An intraventricular injection was performed in the 4ºV region of antagonists of the Glutamate and GABA pathways, where it was observed that they alter the effect of EFA in EG. Angiotensin II (ANGII) was also measured in the blood of exercised and sedentary rats. In the other experimental protocols, the animals were pre-treated 30 min before the EFA protocol with vehicle (1ml) or with Alisquireno (ALQ) (50 mg / kg), Captopril (CAP) (5 mg / kg), Losartana (LOS ) (10 mg / kg) and Spironolactone (ESP) (50mg / kg) via ip An increase in the concentration of ANGII in the blood of the EFA group was observed. In the evaluation of gastric retention (RG) it was possible to observe that the EFA increased (p <0.05) when compared to the sedentary group (EDS) and when pretreated the groups with CAP, LOS and ESP reversed the increase in gastric retention promoted by AND FA. When contractility in vitro was performed, the rats in the EFA group showed less responsiveness (p <0.05) to carbacol. For investigation of the enteric nervous system, neurons were marked using the NADH-diaphorase histochemistry technique in the myenteric plexus, where it was possible to observe the EFA group having increased (p <0.05) neural density in this group.